Undertanding's Analysis the Concept of Classification of Living Organism for Student's Class VII at SMPN 8 Padang - Rahmadhani Fitri; Niggita Syofyati; Heffi Alberida (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
Biology is one of the branches of IPA. Biology as one of science subjects has different principles with other science subjects. It has many concepts contained in biology. One of the complex bilogical materials contained in biology and difficult to understand by learners's the material about classification of living things. In addition, the material classification of living things commonly used terms that difficult to understand by learners. Therefore, it is necessary to identify the concepts in the material classification of living things that have not been or have been understood by students. This study aims to analyze the understanding of the concept of classification of living things in class VII students in SMPN 8 Padang. The type of this research is descriptive research. The sample was taken by simple random sampling technique, with 48 students. The research was conducted by giving multiple choice test questions with open reasoning. Data were analyzed quantitatively. The result of the research showed that the students of class VII in SMPN 8 Padang experienced the level of understanding of the concept on the low category. Low comprehension of concepts includes the concepts of the characteristics of living things 41.66%; basic classification of living creatures 25.00%; 12.50% determination key concepts; monera and protista groups 16.93%; features of Kingdom Fungi 21.88%; features of Kingdom Plantae 20.83%; the difference between moss, ferns and seed plants 18.23%; the features of Kingdom Animalia 9.38% and the difference between Vertebrate and Invertebrate animals 16.02%.